Stability of insurance efficiency during the Covid-19 pandemic: A comparative study between Islamic and conventional insurance in Indonesia - Ikhwan, Ihsanul; Rusydiana, Aam Slamet (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – The purpose of this study is to measure and compare The Stability of the efficiency of insurance companies, particularly during the COVID-19 pandemic, at 70 insurance institutions (both sharia and conventional) in Indonesia over Five years, from 2016 to 2020. Methodology – Non-parametric approach, Data Envelopment Analysis (DEA), then extended by Window DEA analysis was employed as the research method. Findings – This study found that COVID-19 has little effect on Insurance efficiency. COVID-19 has a detrimental impact on the efficiency of conventional insurance but does not affect Sharia insurance. This study also found that most Indonesian Insurances are considered the worst performers in terms of efficiency and efficiency stability during the study period. Most of the insurances are included in quadrant IV (low efficiency and high stability). Furthermore, according to the window DEA analysis, the most relatively stable value of Indonesian Insurances is Sinarmas Conventional Insurance Originality – The study that focuses on measuring the efficiency of sharia insurances compared to the efficiency of conventional insurances in Indonesia during the COVID-19 outbreak has never been conducted. This study was the first to measure and compare the efficiency of Indonesian Insurances using the Window DEA analysis.